Rhododendron arboreum of Shivalik Hills: Bridging Traditional Wisdom with Modern Pharmacognostic and In-Vitro Evidences - Devi, Sunita; Rajat; Himani; Prikshit; Ashish; Shilpi (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Rhododendron arboreum is an evergreen shrub or small tree with a showy display of bright red flowers. The name ‘Rhododendron’ is derived from the Greek word ‘RHODO’ means rose & ‘DENDRON' means tree. Rhododendron is the national flower of Nepal & is known as (Laligurans) & the state tree of Uttarakhand. It is called ‘Burans, Bras, Buras or Barahke-phool’ in local dialect. It is widely popular for the processed juice of its flowers which have gained market popularity as rhodo juice sharbat. The plant is found in the Himalayas from Kashmir eastwards to Nagaland. Various parts of the plant exhibited medicinal properties & is used for the treatment of various ailments. The present review is an effort to give the detailed survey of literature on its pharmacognosy, phytochemistry & pharmacological uses of the plant under study.